Perancangan Board Game "Cerna Quest" sebagai Media Edukasi Pembelajaran Sistem Pencernaan untuk Siswa Kelas 5 SD Permata Insani Islamic School - Wiguna, Randy Arya; Prakarsa, Moh. Ali Wisudawan; Setiawardhani, Widya Oktary; Kurnia, Dewi Intan; Hasanah, Zulfah (Jurnal Ragam Pengabdian, 2026)
This project aims to design "Cerna Quest," a board game serving as an interactive educational tool for teaching the human digestive system to 5th-grade students at Permata Insani Islamic School. The project was motivated by the complexity of abstract biological concepts and the prevalence of conventional lecture-based teaching, which often results in poor student retention. The design's key innovation lies in its "knowledge-based movement" mechanic, where player movement is determined by the ability to answer quiz cards—replacing dice to minimize the element of chance. A descriptive qualitative research method was employed alongside the ADDIE (Analysis, Design, Development, Implementation, Evaluation) design model. The final output is a complete board game that integrates clear anatomical illustrations with a challenge-based gameplay system. Through its engaging visual approach, "Cerna Quest" is expected to significantly boost student engagement, motivation, and cognitive understanding. This project offers a creative instructional solution that transforms science education into a meaningful and measurable gaming experience within the school environment.